Szkody wyrządzone przez gołoledź i śnieg na przykładzie Nadleśnictwa Herby, na tle panujących warunków pogodowych w styczniu 2010 roku - Urban, Grzegorz; Gil, Wojciech; Zachara, Tadeusz (Leśne Prace Badawcze, 2011)
At the beginning of 2010 many forests within the Regional Directorate of the State Forests in Katowice were severely damaged by snow and glazed frosts (freezing rain). The Herby Forest District was particularly badly affected. Interference analysis of weather conditions over Europe and Poland, with particular emphasis on the situation in Herby Forest District, indicated that the atmospheric conditions encouraged the formation of snow on 8 th –9 th January 2010. Moreover, freezing rain on 9 th –10 th January 2010 caused extensive glazed frost, which gradually built up and persisted for nearly a day and a half. During the same period, the load on the crown of snow and ice surpassed 40 kg m -2 which far exceeds the critical value for the pine (the main component of local forest stands). The mass of damaged timber was approximately 350000 m 3 of timber and the area of damaged crops and thickets was 313 ha. Pine stands were the most badly affected but young stands of broadleaved species also incurred losses.